KI HAJAR DEWANTARA'S PERSPECTIVE ON CULTURE-BASED EDUCATION IN INDONESIA'S EDUCATIONAL SYSTEM - Indrakurniawan, Machful; Wulandari, Ria; Iffatur Rocmah, Luluk (Antis-Publisher, 2024)
Objective: This study aims to examine and analyze Ki Hajar Dewantara's perspective on culture-based education and its relevance in the context of Indonesia's current education system. Method: Using a qualitative approach and literature review, the study explores the core concepts developed by Ki Hajar Dewantara regarding culture-based education and investigates its application in contemporary education. Results: The findings reveal that Indonesia's current education system tends to prioritize academic achievements and globalization, often sidelining local cultural values. However, the principles of culture-based education as proposed by Ki Hajar Dewantara remain highly pertinent for shaping national character. Integrating cultural values into the curriculum serves not only as a means to preserve cultural diversity and heritage but also as a strategy to nurture a generation with a strong identity capable of thriving in a globalized era. Novelty: This study underscores the enduring relevance of Ki Hajar Dewantara's culture-based education in addressing modern educational challenges. By bridging cultural values and academic achievements, it presents a balanced approach to fostering intellectual intelligence alongside noble character and cultural identity preservation.